THE KINETIC STUDY OF METHYLENE BLUE ADSORPTION USING THE RED FRUIT WASTE BIOCHAR - Yuni Rosita; Ahmad Tawfiequrrahman Yuliansyah; Rochim Bakti Cahyono (Konversi, 2022)
Methylene blue is one of the dyes often used in the textile industry. This dye is toxic which causes environmental pollution and health problems for humans and animals. In this research, adsorption of methylene blue dye was carried out by using an adsorbent in the form of red fruit waste biochar in concentration variations (50, 100, and 150 ppm) and contact times (0, 20, 40, 60, 80, 100 and 120 minutes). The kinetics review modeling was based on the pseudo first order and pseudo second order to determine the adsorption capacity of methylene blue with red fruit waste biochar. The adsorption equation was evaluated using the Langmuir adsorption isotherm and the Freundlich adsorption isotherm. The results showed that the most suitable adsorption equilibrium model followed the Langmuir adsorption isotherm with an equilibrium constant (K) is 0.0510 and the maximum adsorption capacity (Qm) is 0.0048 mg/g. The kinetics model of the methylene blue adsorption reaction based on the pseudo second order with the value of k is 0.6973 min-1 and a relation coefficient value of R2 = 1.